Teaching Arabic Language and Its Problems - Abdul Halim (Britain International for Academic Research (BIAR) Publisher, 2024)
Arabic Leanguae for Indonesian society be really as foreign language, so that process to learn, it always meets the difficulties and problems. That problems and difficulties can stem the existence of differences between the language of Arabic and Indonesian, both in phoneme aspect, morpheme and syntax, and also meaning aspect. The factors influencing the instruction of Arabic language are linguistic factors, psychological factors, learning factors and methods of individual factors and instructions and lesson items.